Medical texts made simple - dream or reality? - Askehave, Inger; Zethsen, Karen Korning (HERMES - Journal of Language and Communication in Business, 2000)
This article is concerned with some of the problems medical companies have in trying to produce user-friendly medical texts. Research has shown that consumer information within the medical field is often difficult to understand for the non-specialist. There are several reasons for this. One is the frequent use of special language features in texts concerned with consumer information. This article discusses the advantages and disadvantages of special language and suggests ways in which specialist words and expressions may be downgraded and simplified in order to accommodate the intended non-specialist target group.